Optimalisasi Peran Tokoh Masyarakat dan Kepala Kampung Dalam Pengabdian Berbasis Edukasi Pariwisata Kampung Malaus: Pengabdian - Friska Putri Purwitasari; Syifaul Fauziah; Nur Khozin Wahyu Hidayatullah; Andi Fachry Army Saputra; Muhammad Royhan Al-Kais; Siti Fatimah Azzahra; Nila Amanda Dinilah; Aryadhy; Ahmad Taufik Hidayah; Rusyaid; Ashari (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service research aims to optimize the role of local leaders and the Village Head in strengthening community-based tourism education in Malaus Village. The initiative responds to the limited tourism literacy among residents and the lack of effective coordination within local leadership in developing the village dam as both an educational and recreational site. Using a descriptive qualitative approach, data were collected through participatory observation, in-depth interviews, and documentation involving the village head, RT/RW leaders, fish-cage managers, youth groups, and community members as key informants. The findings reveal that local leaders act as social facilitators who successfully mobilize community participation, while the Village Head provides policy legitimacy and structured direction for tourism development. Student involvement serves as a catalyst that enhances practical educational activities, including site cleaning, environmental arrangement, and digital content training for local youth. The results indicate that the success of tourism education is strongly influenced by active local leadership, community social capital, and synergy among village stakeholders.